Financial structures and the real effects of credit-supply shocks in Denmark 1922-2011 - Kim Abildgren (European Central Bank (ECB), 2012)
We examine the real effects of credit-supply shocks using a series of structural vector autoregressive models estimated on the basis on a new quarterly data set for Denmark spanning the past 90 years or so. We find no effects on the unemployment level from supplyshocks to credit from commercial/savings banks in the periods 1922-1949 and 1981-2011 even though these periods contained several cases of severe banking and financial crises. Furthermore, credit-supply shocks do not seem to explain any significant share of the volatility in the unemployment rate during these periods. We attribute these findings to the large market for mortgage-credit loans in Denmark raised through bond-financed mortgage banks combined with comprehensive government interventions to safeguard financial stability during times of crises. There might, however, be indications of real effects from credit-supply shocks in the period 1950-1980 where credit rationing and exchange controls served as important economic-policy instruments. Overall these results indicate that both the financialsystem structure as well as the extent of government intervention during banking crises play a key role to the significance of real effects of credit-supply shocks. These findings must be kept in mind when modelling the role of financial intermediaries in macroeconomic models.
Keywords: C32; E51; N14; 330; banking and financial crises; Credit-supply shocks; Danish economic history; vector autoregressions